Upaya Penanganan Nyeri Pinggang Pada Ibu Hamil Trimester Ke-III Di Puskesmas Grogol Sukoharjo - NURTIYANA, EVI, Winarsih Nur Ambarwati, S.Kep,Ns,ETN,M.Kep (2016)
Background: Low back pain is a nuisance experienced by many pregnant women who do not only occur in a particular trimester, but can be experienced throughout the period of pregnancy until the post-natal period. Low back pain in pregnant women is influenced by several factors: changes in posture, edistribusi ligaments, your center of gravity shifts forward, and when combined with stretching of the abdominal muscles are weak. Objective: Authors can cope with back pain in the third trimester pregnant women in accordance with the standards of nursing care. Methods: The method used is descriptive case study approach, is to perform nursing care in patients with back pain in pregnancy trimester of three ranging from assessment, intervention, implementation, and evaluation of nursing. Results: After 3x24-hour nursing care in patients with back pain in pregnancy trimester back pain problems can be resolved partially and continued intervention. Conclusion: Nursing problems that occur in patients can be overcome in part so that interventions need to be in advanced.